Communicative Language Teaching in a Non-Urban Madrasah Aliyah: A Qualitative Case Study of Students’ Speaking Development at Madrasah Aliyah Ittihadul Bayan Telaga Lebur Sekotong: English - Muhammad Hilmi (JOEY: Journal of English Ibrahimy, 2026)
Speaking ability in English is an essential communicative skill in responding to the demands of globalization; however, it remains a challenge for students in Indonesia, particularly at the Madrasah Aliyah level in rural areas. Low student participation in speaking English and the dominance of conventional teaching methods indicate the need for a more communicative and contextual learning approach. Therefore, this study aims to explore and describe the implementation of Communicative Language Teaching (CLT) in improving students’ speaking ability at Madrasah Aliyah Ittihadul Bayan Telaga Lebur Sekotong. This research employed a qualitative approach with a case study design. The data were collected through classroom observations, in-depth interviews with teachers and students, and documentation, and were analyzed thematically. The findings reveal that the implementation of CLT through communicative activities such as pair work, group discussions, and role play was able to enhance students’ courage, activeness, and self-confidence in speaking English. In addition, CLT created a more collaborative classroom atmosphere and encouraged students to perceive speaking as a process of communication rather than mere memorization. This study concludes that CLT is effectively implemented in the Madrasah Aliyah context and provides important implications for the development of more communicative English language teaching. Future research is recommended to examine the implementation of CLT in a broader madrasah context and to combine qualitative and quantitative approaches in order to obtain a more comprehensive understanding.